2003
DOI: 10.1210/jc.2003-030672
|View full text |Cite
|
Sign up to set email alerts
|

The −3826 A→G Variant of the Uncoupling Protein-1 Gene Diminishes Postprandial Thermogenesis after a High Fat Meal in Healthy Boys

Abstract: This study investigated whether the -3826 A-->G nucleotide variant of the uncoupling protein-1 (UCP1) gene is correlated with postprandial thermogenesis after a high fat meal in children. Healthy boys, aged 8-11 yr, were examined for resting energy expenditure and the thermic effect of a meal (TEM), which were measured by indirect calorimetry for 180 min after a high fat (70% fat, 20% carbohydrate, and 10% protein, providing 30% of the daily energy requirement) and a high carbohydrate meal (20% fat, 70% carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 18 publications
4
44
3
Order By: Relevance
“…Accordingly, diminished REE observed in G-allele carriers may be caused primarily by attenuated UCP1-linked thermogenesis. This finding appears to be inconsistent with our previous pediatric studies 10,11 that there were no significant effects of this polymorphism on baseline REE in healthy children. This discrepancy may be explained by the difference in the age of the subjects; that is, they were 8-11 (Nagai et al 10 ) or 6-10 (Nagai et al 11 ) years old in the previous studies, being younger than those in the present study (20-22 years old).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Accordingly, diminished REE observed in G-allele carriers may be caused primarily by attenuated UCP1-linked thermogenesis. This finding appears to be inconsistent with our previous pediatric studies 10,11 that there were no significant effects of this polymorphism on baseline REE in healthy children. This discrepancy may be explained by the difference in the age of the subjects; that is, they were 8-11 (Nagai et al 10 ) or 6-10 (Nagai et al 11 ) years old in the previous studies, being younger than those in the present study (20-22 years old).…”
Section: Discussioncontrasting
confidence: 99%
“…10,11 After the phenol-extraction procedure, 0.2-2 mg of DNA was obtained per subject. The -3826A/G polymorphic region of UCP1 (rs1800592) was amplified using the PCR with a sense primer (5 0 -TTT GTG CAG CGA TTT CTG ATT GAC-3 0 ), an anti-sense primer (5 0 -AGG AGT GGC AGC AAG TTC TGA ATG-3 0 ) and a primer labeled at the 5 0 end with Texas red (5 0 -AAA TGC ACT CGA TCA AAC TGT-3 0 ).…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…29 As the sympathetic branch of the autonomic system particularly contributes to coordinating energy homeostasis, any alteration in sympathetic nervous system is widely assumed to promote onset and development of obesity. 14,30 Nagai et al 30 showed that the complete autonomic blockade evaluated by means of PSA of HRV significantly reduced the energy expenditure in humans. In addition, Heinonen et al 1 found that the Glu 9 /Glu 9 genotype was associated with reduced basal metabolic rate in obese Finns population.…”
Section: Discussionmentioning
confidence: 99%
“…In small mammals, its role in sympathetic control of thermoregulatory thermogenesis is well established, and its role in the control of DIT seems to be intimately linked, and secondary, to its role in thermal regulation. In humans, however, the notion that UCP1 is involved in DIT has been largely abandoned, although recent findings that children with UCP1 polymorphism (GG allele carriers) have lowered postprandial thermogenesis in response to a high-fat meal [94], raises the possibility that such UCP1-linked thermogenesis may have relevance for childhood obesity.…”
Section: Is There a Role For Uncoupling Proteins In Fat Metabolism Anmentioning
confidence: 99%